2022
DOI: 10.3390/metabo12030218
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome, Mycobiome and Related Metabolites Alterations in Patients with Metabolic Syndrome—A Pilot Study

Abstract: Metabolic syndrome (MetSyn) has a rapidly growing worldwide prevalence, affecting over 1 billion people. MetSyn is clustering many pathological conditions, which, untreated, could increase the risk and often lead to more severe metabolic defects such as type 2 diabetes and non-alcoholic fatty liver disease. Many data demonstrate the complex role of gut microbiota in the host metabolism, and hence, deciphering the microbiome patterns linked to MetSyn could enable us for novel diagnosis and monitoring markers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Moreover, metformin was reported to increase the abundance of A. muciniphila in the gut [ 50 ]. We have previously shown that A. muciniphila abundance is decreased in patients with metabolic syndrome [ 25 ] and we show here that this microbe is significantly reduced in the T2D-associated microbiota. Similar to our findings, Akkermansia abundance was shown to be decreased in Chinese T2D [ 51 ] as well as in a prediabetes Danish cohort [ 27 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, metformin was reported to increase the abundance of A. muciniphila in the gut [ 50 ]. We have previously shown that A. muciniphila abundance is decreased in patients with metabolic syndrome [ 25 ] and we show here that this microbe is significantly reduced in the T2D-associated microbiota. Similar to our findings, Akkermansia abundance was shown to be decreased in Chinese T2D [ 51 ] as well as in a prediabetes Danish cohort [ 27 ].…”
Section: Discussionsupporting
confidence: 68%
“…In this cross-sectional study, we report significant modifications of the gut microbiome in T2D individuals. We have previously reported that patients with metabolic syndrome have a microbiome enriched in Enterobacteriaceae [ 25 ]. Herein, we show that the microbiome of T2D patients is significantly increased in Enterobacteriaceae , a family of facultatively aerobic microorganisms generally viewed as a marker of gut dysbiosis and inflammation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, we analyzed the relationship between gut luminal succinate and intestinal flora in samples from human neonates and mouse pups. Our data indicated that there were significantly higher proportions of succinate-producing bacteria, including Enterococcaceae and Escherichia_Shigella ( Gradisteanu Pircalabioru et al., 2022 ), and significantly lower proportions of succinate-consuming bacteria, including Staphylococcaceae , Lactobacillaceae , Staphylococcus and Lactobacillus ( Shima et al., 2022 ) in human neonates with NEC than in control human neonates. Among the model mice, there were significantly higher proportions of succinate-producing bacteria, including Enterococcaceae , Clostridiaceae , Clostridium_sensu_stricto_1 , and Enterococcus ( Phuengjayaem et al., 2020 ) and significantly lower proportions of succinate-consuming bacteria including Lactobacillaceae and Lactobacillus ( Shima et al., 2022 ) in mice with NEC than in those without NEC.…”
Section: Discussionmentioning
confidence: 74%
“…Fungi also release metabolites, such as candidalysin, which serve as a cytotoxin that promotes antifungal inflammatory responses and immune system cascades [ 71 ]. Additionally, it has been observed that changes in the mycobiome, which then change the bacterial microbiome, can influence critical metabolites within the body, such as short-chain fatty acids, organic acids, taurine, butyrate, and succinate [ 72 ]. Furthermore, metabolites produced directly by mycobiome fungal colonizers have been linked to shaping host health with metabolic diseases and cancers associated with changes in fungal metabolites [ 53 ].…”
Section: Discussionmentioning
confidence: 99%